2011
DOI: 10.1089/lap.2010.0101
|View full text |Cite
|
Sign up to set email alerts
|

New Berlin-Buch “Reversed Nuss,” Endoscopic Pectus Carinatum Repair Using Eight-Hole Stabilizers, Submuscular CO2, and Presternal Nuss Bar Compression: First Results in 35 Patients

Abstract: Although this is a very early experience, "reversed Nuss" is safe and effective and new technical improvements have expanded the range of applicability to older patients and suitable redos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
(8 reference statements)
0
16
0
Order By: Relevance
“…In the last few years, a plethora of procedures using minimal access techniques for PC correction have been published [14][15][16][17][18][19][20]. These procedures, now popularly known as the "Abramson" or "reverse Nuss" procedures, are associated with unclear indications, have shown variable results, and are simply too new to judge [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, a plethora of procedures using minimal access techniques for PC correction have been published [14][15][16][17][18][19][20]. These procedures, now popularly known as the "Abramson" or "reverse Nuss" procedures, are associated with unclear indications, have shown variable results, and are simply too new to judge [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…These procedures, now popularly known as the "Abramson" or "reverse Nuss" procedures, are associated with unclear indications, have shown variable results, and are simply too new to judge [14][15][16][17][18][19][20]. Many of their technical details are still being worked out.…”
Section: Discussionmentioning
confidence: 99%
“…It is agreed by physicians that, for the PC/PE correction through the MIS approach, the corrective bar must be placed, respectively, above/below the sternum's most prominent region (Schaarschmidt et al 2011;Yiiksel et al 2011). Thus, the relation between the corrective bar positioning along the sternum and the distribution of the stresses generated on the ribs' backend was investigated.…”
Section: Rib Cage Sternummentioning
confidence: 99%
“…Only more recently, a MIS approach for PC has been investigated (Abramson et al 2009;Schaarschmidt et al 2011;Yiiksel et al 2011) based on the Nuss technique, on which the corrective bar is placed under the skin and on top of the sternum highest protrusion point for its continuous compression, and fixed on both sides of the chest wall.…”
Section: Introductionmentioning
confidence: 99%
“…-Mini-invasive submuscular dissection (Schaarschmidt et al, 2006): the pectoralis muscle dissection is performed by subpectoral CO2 insufflation, the resection of the ribs, the sternal osteotomy and the insertion of trans-sternal steel struts are performed through a vertical pre-sternal incision under endoscopic view. Recently, the same Authors reported some technical variations (Schaarschmidt et al, 2011), abandoning the presternal incision and performing a more extense submuscular dissection and two lateral incisions between the anterior and middle axillary lines. These should allow the creation of a submuscular and presternal tunnel in order to implant a Nuss metal bar presternally.…”
Section: Treatment Optionsmentioning
confidence: 99%